SOSIALISASI PELATIHAN PENYUSUNAN HPP BERBASIS DIGITAL TRAINING - Rosy Armaini; Anisah Adiva Utami; Yevi Dwitayanti; Sri Hartaty; Faridah (Politeknik Negeri Sriwijaya, 2023)
Abstract The PKM Team's program this time is socialization on how to conduct training in compiling computerized CGP, through digital training at Pempek and Martabak Ato’ Semeru Mitra. This is done because the conditions in 2022 are the initial stages of MSMEs starting to rise, as the influence of Covid19 decreases. Even so, there are still many people who choose to do activities as needed outside. Therefore, the PKM Team agreed to introduce easy training in compiling Cost of Production, through digital training. We start this training by designing HPP calculations using Visual Basic for Application. Then the PKM Team packs it in a Video Tutorial which is complete with usage examples. Furthermore, the training continues with the help of Gmeet or Zoom. Partners are greatly helped by this training, because after studying the material before the training begins, the tutorial time is fully used for Q&A in numerical simulations, so Partners are able to produce a Cost of Goods Production Report. Keywords: CGP, Digital Training